Efficacy of Ceftazidime-Avibactam Versus Polymyxin B and Risk Factors Affecting Clinical Outcomes in Patients With Carbapenem-Resistant Klebsiella pneumoniae Infections a Retrospective Study - Fang, Jie; Li, Hui; Zhang, Min; Shi, Guochao; Liu, Mengying; Wang, Yujie; Bian, Xiaolan (Frontiers in Pharmacology, 2021)
Background. The worldwide outbreak of carbapenem-resistant Klebsiella pneumoniae (CRKP) has become an urgent public health problem. High mortality and lack of effective treatments further pose new challenges to control this infection. However, studies about the evaluation of available antibiotics for CRKP infection are limited. The present study aimed to compare the efficacy of polymyxin B versus ceftazidime-avibactam (CAZ/AVI) in Chinese patients with CRKP infections and to identify risk factors affecting 7-day bacterial eradication and 28-day all-cause mortality. Methods. From January 8, 2018, to July 6, 2020, a total of 115 adult CRKP infected patients from two tertiary teaching hospitals in Shanghai, China were enrolled based on the inclusion and exclusion criteria. By reviewing electronic medical records of these patients, demographic and clinical data were extracted. The selected patients were divided into polymyxin B and CAZ/AVI groups according to primary antibiotic exposure to compare therapeutic effects. Binary logistic and cox’s regression analysis were performed to identify risk factors for 7-day bacterial eradication and all-cause mortality. Results. One hundred and five patients were treated with polymyxin B (67.8%) or CAZ/AVI (32.2%). Patients in the CAZ/AVI group had significantly lower rates of 28-day mortality (8.1% vs 29.5%, p=0.013), higher microbiological eradication and 28-day clinical success. Multivariate analysis showed that Charlson comorbidity index (≥3) and prior antibiotic use within 90 days were independent risk factors for poor microbiological eradication. Cox’s regression analysis indicated that the length of hospitalization after CRKP infection and baseline creatinine clearance negatively affected 28-day mortality. Conclusion. CAZ/AVI was more effective than polymyxin B and appeared to be a promising drug for CRKP infection, especially for critically ill patients.